Children in Vegetative State and Minimally Conscious State: Patients' Condition and Caregivers' Burden. (2nd February 2012) - Giovannetti, A. M.; Pagani, M.; Sattin, D.; Covelli, V.; Raggi, A.; Strazzer, S.; Castelli, E.; Trabacca, A.; Martinuzzi, A.; Leonardi, M.
Abstract : Caring for children in vegetative state (VS) or minimally conscious state (MCS) challenges parents and impacts on their well-being. This study aims to evaluate caregivers' health condition, coping, anxiety and depression levels, and how these issues relate to children's disability. 35 children with VS and MCS were administered the disability rating scale (DRS) and 35 caregivers completed the Coping Orientations to Problem Experiences, Short Form-12, Beck Depression Inventory, and the Spielberger State-Trait Anxiety Inventory-Y. Children were mainly males (68.6%), hosted at domicile (77.1%), and diagnosed with VS (60%), with anoxic aetiology (45.7%). Caregivers were mainly mothers (85.7%), married (82.9%), and housewives (51.4%); 60% declared financial difficulties, and 82.9% provided full-time assistance. 57.2% reported depressive symptoms, poor mental health, and high level of state and trait anxiety. "Problem-oriented" (P < 0.001 ) and "emotional-oriented" (P < 0.001 ), were more adopted than "potentially dysfunctional" ones. DRS scores (mean = 22.0; SD = 1.9) did not significantly correlate to any psychological measure. Rehabilitative programs for children with SV and SMC should also provide interventions on surrounding systems: improving the network of psychological support and social assistance may decrease the burden of caregivers and, in turn, improve caring abilities and children quality of life.